Digital Marketing dalam Perspektif Ekonomi Islam - Suci Hartini; Fasa, Muhammad Iqbal; Suharto (Jurnal Ekonomika dan Bisnis Islam, 2022)
Digital Marketing In Islamic Economic Perspective. Marketing is an activity in which sellers offer products that consumers can buy. While Islamic marketing is a process and strategy (wisdom) of fulfilling needs through halal products and services (tayyibat) with mutual agreement and welfare (Falah from both parties, namely buyers and sellers for the purpose of achieving material and spiritual prosperity in this world and in the hereafter). In digital marketing with an Islamic perspective, all activities related to the technology must be based on sharia law. Just as digital activities are not allowed to contain usury (interest), activities in cyberspace do not contain maisir (gambling), activities involving the manufacture and/or sale of illicit products are prohibited, and the prohibition on activities containing elements of gharar (uncertainty).